Representasi Kasih Sayang Ayah Pada Anak Dalam Video Klip "Saat Kau Telah Mengerti" (Analisis Semiotika Charles Pierce) - Abdullah, Umar; Riski Apriliani (CARAKA : Indonesia Journal of Communication, 2024)
Video clips are a form of communication that conveys messages using audio visuals. The messages conveyedhave meaning and purpose. This study aims to determine how communication between father and child isrepresented in the video clip of Virgoun's song entitled Saat Kau Telah Mengerti. This study uses CharlesSanders Peirce's Semiotic analysis to determine the meaning of the signs displayed in this video clip. Datawere obtained from a collection of documentation literature and library studies. The researcher achievedthis by carefully examining, paying attention to, and documenting the situation in the video clip of Virgoun'ssong Saat Kau Telah Mengerti which is relevant to the research objectives, namely to find out more aboutthe interaction between father and child in the video clip. The sampling technique used in this study was apurposive sampling technique, namely the sample was selected according to the criteria determined by theresearcher. The results of this study found that the form of a father's affection for a child is very crucial forthe child and has an important role in the child's life, especially in terms of providing a sense of security andaffection so that the child feels loved and appreciated so that the child can grow well, independently andresiliently.